Mais Médicos (More Doctors) Program: the evolution of medical production indicators in the basic healthcare service of a mid-sized county in Espírito Santo State (Brazilian Journal of Health Research, 2021)
Introduction:The structural axes of Mais Médicos (More Doctors) Program (“Programa Mais Médicos - PMM)” comprises doctors focusing on the treatment cases of emergency in vulnerable areas. Objective: Evaluating the evolution of medical production indicators in the basic healthcare service of a mid-sized county, after PMM implementation. Methods: Descriptive, longitudinal and epidemiological study. Data available at SIAB, Consulfarma and about Aracruz County (ES) were used to obtain variables associated with medical productivity (number of physicians, population coverage and medical consultations in primary healthcare per age group, childcare and prenatal consultations and home visits). Frequencies concerning the assessed variables were calculated by taking into consideration 2 periods-of-time, namely: before and after PMM. Results: The number of physicians hired through PMM was considerably larger than that of other contract types, in the course of time. Only physicians linked to the program worked in the county (15) in 2016, which reduced population coverage from 74.7% (before PMM) to 69.1% (after PMM). The number of medical consultations has increased for most age groups and decreased for children younger than 4 years. There was increased number of childcare (24%) and prenatal (39%) appointments, and home visits (950%). Conclusion: There was positive increase in the number of consultations; at the end of the analyzed period, the decreased number of doctors resulted in decreased population coverage.
Keywords: Doctor; Family Health Strategy; Primary Care; Mais Médicos Program; Health Policy